Ship handling - House, D. J. (Routledge, 2007)
Suitable as a training manual and a day-to-day reference, Shiphandling is the comprehensive and up to date guide to the theory and practice of ship handling procedures. Its covers the requirements of all STCW-level marine qualifications, provides expert guidance on all the hardware that marine professionals will make use of in the control and operation of their vessel and offers a broad focus on many shiphandling scenarios.